2017
DOI: 10.1016/s2214-109x(17)30142-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy infection with hepatitis B virus and the risk of preterm birth: a population-based cohort study

Abstract: Chinese Association of Maternal and Child Health Studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 33 publications
10
111
1
1
Order By: Relevance
“…NFPHEP was launched by the Chinese National Health and Family Planning Commission and the Ministry of Finance in 2010 to provide free preconception health examinations and counselling services for couples of reproductive age in rural areas who planned to become pregnant within the next 6 months. Project‐related design, organization and implementation have been described previously . This study was approved by the Institutional Review Board of the Chinese Association of Maternal and Child Health Studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NFPHEP was launched by the Chinese National Health and Family Planning Commission and the Ministry of Finance in 2010 to provide free preconception health examinations and counselling services for couples of reproductive age in rural areas who planned to become pregnant within the next 6 months. Project‐related design, organization and implementation have been described previously . This study was approved by the Institutional Review Board of the Chinese Association of Maternal and Child Health Studies.…”
Section: Methodsmentioning
confidence: 99%
“…China has the world's largest burden of HBV infection in the world with an estimated 74.6 million chronically infected . Recent studies have reported a prevalence of HBV infection in China of 4.3%‐6.3% . Blood‐borne transmission is one of the major routes of HBV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 39 348 119 reproductive‐age (20–49 years) participants participated in this program between 2010 and 2015 and were eligible for this study when excluding individuals with missing data that were used to estimate air pollution exposure or used in the concentration‐response relationship analysis. Detailed project‐related design, organization, and implementation have been previously described . The research proposal was approved by the ethics committee of National Research Institute for Health and Family Planning.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed project-related design, organization, and implementation have been previously described. [17][18][19][20] The research proposal was approved by the ethics committee of National Research Institute for Health and Family Planning. All participants provided written informed consent.…”
Section: Study Populationmentioning
confidence: 99%